2021
DOI: 10.1002/essoar.10503161.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon dioxide distribution, origins, and transport along a frontal boundary during summer in mid-latitudes

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…The 8/4/2016 frontal case shows a narrow, elevated [CO 2 ] band at the frontal boundary (∼25 ppm difference in [CO 2 ] across the front). We examined this frontal case with a 3 × 3‐km (cloud‐resolving) resolution model and showed that this elevated [CO 2 ] band has a maximum width of ∼200 km and a length of over 800 km extending from northeastern Kansas to northeastern Iowa (Samaddar et al., 2021). Figure 2 shows that the frontal boundaries are associated not only with elevated [CO 2 ] but also with highly variable [CO 2 bio].…”
Section: Resultsmentioning
confidence: 99%
“…The 8/4/2016 frontal case shows a narrow, elevated [CO 2 ] band at the frontal boundary (∼25 ppm difference in [CO 2 ] across the front). We examined this frontal case with a 3 × 3‐km (cloud‐resolving) resolution model and showed that this elevated [CO 2 ] band has a maximum width of ∼200 km and a length of over 800 km extending from northeastern Kansas to northeastern Iowa (Samaddar et al., 2021). Figure 2 shows that the frontal boundaries are associated not only with elevated [CO 2 ] but also with highly variable [CO 2 bio].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Samaddar et al. (2021) attributed the elevated CO 2 mole fractions along the frontal boundary to continental biogenic CO 2 fluxes. Samaddar et al.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated CO 2 band (416 ppm) was found at the frontal boundary, similar to results from the summer‐2016 campaign (Figure 3a ). This phenomenon appears closely tied to biological CO 2 fluxes (Samaddar et al., 2021 ), perhaps particularly respiratory fluxes (Hu et al., 2021 ). CO and CH 4 mole fractions were higher in the cold sector than in the warm sector (Figures 3d and 3e ), likely indicative of large CH 4 emissions from animal agriculture in the upper Midwest and perhaps larger upwind anthropogenic CO sources in the upper Midwest (analyses in preparation).…”
Section: Applications Of Act‐america Datamentioning
confidence: 94%
“…The ACT‐America team is analyzing how GHG distributions change vertically and horizontally across frontal boundaries (e.g., Pal et al., 2020a ), and is comparing these observations to numerical simulations (Gerken et al., 2021 ; Samaddar et al., 2021 ). The 20 June 2019 RF described in Section 1.1 is an excellent illustration of the information available in one such flight.…”
Section: Applications Of Act‐america Datamentioning
confidence: 99%
See 1 more Smart Citation